Relevance of risk management in the supply chain: practical results and lessons learned - Sablón Cossío, Neyfe (2022)
The objective of this article is to value the relevance of risk management in supply chains. That is why a group of tools for risk analysis and evaluation were selected and applied in a stakeholder process of a Cuban real estate chain. It was realized using the BestLog case method. The study is classified as qualitative, descriptive and exploratory. It was realized a study of seven tools for the identification of risk with the study of the literature on this subject. The principal results are the identification of the attributes of each tool and the risk matrix of this study case. The theoretical value of this work is the systematization of risk tools, and the practical value is focused on determining actions to mitigate risks in the Cuban case study, and also learning lessons after the initial application of the selected tool.